(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
Two new symmetric azomethine dyes capable of photoinduced isomerization were synthesized by condensing symmetric bis-aldehyde (obtained by the reaction of epichlorohydrin with 4-oxybenzaldehyde) with 4-nitroaniline and 4-chloroaniline, respectively. The yield of the target products decreases with the transition from nitro-substituted azomethine to chlorine-substituted. This is due to the greater basicity of the starting amines with nitro-substitution when increasing the acceptor force of the substituent complicates the course of the reaction. Azomethines are characterized by absorption with a maximum at 400–410 nm, which makes them sensitive to radiation with a blue component of the spectrum. The photoelectric properties of azomethines upon irradiation were investigated by the method of measuring the surface potential with the help of a Kelvin dynamic probe. The maximum value of the electric potential of the photosensitive films free surface during irradiation with white LED at I = 60 W/m2 is about 270 mV in the case of azomethine with a nitro group in the 4,4’ position and about 125 mV in the case of azomethine with chlorine as a substituent. That is, the magnitude of the electric potential of the free surface decreases approximately twice during the transition from nitro substituent to chlorine. This may be explained by the fact that the photoinduced changes in azomethine with a higher acceptor substituent flow more quickly and with greater efficiency. But at the same time, the reverse changes when turning off the light are just as fast. For chlorine substituted azomethine samples, the reverse process proceeds rather slowly, which may indicate greater stability over time of the photochemically modified form in case of chlorine substitution compared to the nitro-substituted analogue. Thus, the synthesized azomethines can be used in the development of new photovoltaic media and recording media for optical information recording.